(untitled) (Journal of EAHIL, 2025)
This paper describes the motivation, development and results of the workshop “Spotting Sharks in the Ocean of Academic Publishing: How to Steer Clear of Predatory Behaviour”. The workshop was developed in response to questions from researchers who had published in a journal that later turned out to be unreliable or who questioned a journal’s quality when selecting a publication venue. The goal is to teach researchers how to make the distinction between reliable and untrustworthy journals and reduce distrust of new or smaller publishers. The session was developed at KU Leuven and then adapted for presentation at the EAHIL conference. It provided valuable insights into raising awareness, fostering collaboration among research support staff, and strengthening trust in the publishing landscape.